A dynamic theory of public spending, taxation and debt - Marco Battaglini; Stephen Coate (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
This paper presents a dynamic political economy theory of public spending, taxation and debt. Policy choices are made by a legislature consisting of representatives elected by geographically-defined districts. The legislature can raise revenues via a distortionary income tax and by borrowing. These revenues can be used to finance a national public good and district-specific transfers (interpreted as pork-barrel spending). The value of the public good is stochastic, reflecting shocks such as wars or natural disasters. In equilibrium, policy-making cycles between two distinct regimes: business-as-usual in which legislators bargain over the allocation of pork, and responsible-policy-making in which policies maximize the collective good. Transitions between the two regimes are brought about by shocks in the value of the public good. In the long run, equilibrium tax rates are too high and too volatile, public good provision is too low, and debt levels are too high. In some environments, a balanced budget requirement can improve citizen welfare.
Keywords: 330; Dynamisches Modell; Öffentliche Ausgaben; Steuerpolitik; Öffentliche Schulden; Wohlfahrtseffekt; Public Choice; Theorie